A comprehensive meta‐analysis of stem cell therapy for chronic angina. Issue 4 (17th April 2018) - Shah, Rahman; Latham, Samuel B.; Khan, Sajjad A.; Shahreyar, Muhammad; Hwang, Inyong; Jovin, Ion S.
Abstract : Background: A substantial proportion of patients with coronary artery disease do not achieve complete revascularization and continue to experience refractory angina despite optimal medical therapy. Recently, stem cell therapy has emerged as a potential therapeutic option for these patients. However, findings of individual trials have been scrutinized because of their small sample sizes and lack of statistical power. Therefore, we conducted an updated comprehensive meta‐analysis of available randomized controlled trials (RCTs) with the largest sample size ever reported on this subject. Hypothesis: In patients with chronic angina stem cell therapy improves clinical outcomes. Methods: Scientific databases and websites were searched for RCTs. Data were independently collected by 2 investigators, and disagreements were resolved by consensus. Data from 10 trials including 658 patients were analyzed. Results: Stem cell therapy improved Canadian Cardiovascular Society angina class (risk ratio: 1.53, 95% CI: 1.09 to 2.15, P = 0.013), exercise capacity (standardized mean difference [SMD]: 0.56, 95% CI: 0.23 to 0.88, P = 0.001), and left ventricular ejection fraction (SMD: 0.63, 95% CI: 0.27 to 1.00, P = 0.001) compared with placebo. It also decreased anginal episodes (SMD: –1.21, 95% CI: –2.40 to −0.02, P = 0.045) and myocardial perfusion defects (SMD: –0.70, 95% CI: –1.11 to −0.29, P = 0.001). However, no improvements in all‐cause mortality were observed after a relatively short follow‐up. Conclusions: In patients with chronic angina on optimal medical therapy, stem cell therapy improves symptoms, exercise capacity, and left ventricular ejection fraction. These findings warrant confirmation using larger trials.